A NOVEL P.ASP304GLY MUTATION IN BEST1 GENE ASSOCIATED WITH ATYPICAL BEST VITELLIFORM MACULAR DYSTROPHY PHENOTYPE AND HIGH INTRAFAMILIAL VARIABILITY. Issue 9 (September 2016) - Peiretti, Enrico; Caminiti, Giulia; Forma, Gina; Carboni, Giovannella; Dhaenens, Claire-Marie; Querques, Lea; Souied, Eric; Querques, Giuseppe
Abstract : Purpose: To report the atypical phenotypic characteristics of patients with a novel p.Asp304Gly mutation in BEST1 . Methods: Affected individuals underwent a complete ophthalmic examination, including best-corrected visual acuity, fundus autofluorescence, spectral domain optical coherence tomography, and electrophysiologic testing. All individuals were screened for mutations in the BEST1 gene. Results: Five patients of the same Italian family were clinically examined. All patients complained of decreased vision as the initial symptom. Best-corrected visual acuity ranged from 20/800 to 20/32. On fundus examination, all patients showed atypical Best vitelliform macular dystrophy phenotype with multifocal macular and extramacular involvement. The spectral domain optical coherence tomography characteristics of central macular and extramacular lesions varied in each patient and included "giant" choroidal excavation, extensive flat macular elevation with hyporeflective subretinal material accumulation surrounded by hyperautofluorescent spots/annulus, and extensive hypoautofluorescent extramacular atrophic areas. Electrooculogram was always abnormal with Arden ratio lower than 1.55, whereas electroretinogram was normal in the two younger patients and abnormal (low amplitude) in the three older patients. Genetic analysis revealed a novel missense mutation in BEST1, substituting aspartate for glycine at amino acid 304. Conclusion: We describe the atypical phenotype and high intrafamilial variability associated with a new mutation in the BEST1 gene in an Italian family affected with Best vitelliform macular dystrophy. Clinicians should consider screening the BEST1 gene even in the absence of the typical phenotype and in case of high intrafamilial variability. Abstract : The authors describe the atypical phenotype (including multifocal lesions, "giant" choroidal excavation, extensive flat macular elevation, and extramacular atrophic areas) and high intrafamilial variability associated with a novel p.Asp304Gly mutation in the BEST1 gene in an Italian family affected with Best vitelliform macular dystrophy.